Trans-sialidase neutralizing antibodies detection in Trypanosoma cruzi infected domestic reservoirs. - Sartor, Paula Andrea (2011)
The detection of Trypanosoma cruzi infection in domestic dogs and cats is relevant to evaluating human transmission risks and the effectiveness of insecticide spraying campaigns. However, the serological assays routinely used are associated with cross-reactivity in sera from mammals infected with Leishmania spp. We used a trans-sialidase inhibition assay (TIA) for T. cruzi diagnosis in serum samples from 199 dogs and 57 cats from areas where these types of infections are endemic. TIA is based on the antibody neutralization of recombinant trans-sialidase, an enzyme that is not detected in the coendemic Leishmania species or Trypanosoma rangeli parasites. T. cruzi infection was also evaluated by conventional serology (CS) (indirect immunofluorescence, indirect hemagglutination, enzyme-linked immunosorbent assay, and immunochromatographic dipstick test) and xenodiagnosis. Sera from 30 dogs and 15 cats from areas where these organisms are not endemic and 5 dogs with visceral leishmaniasis were found to be nonreactive by TIA and CS. Samples from dogs and cats demonstrated 91 and 95% copositivities between TIA and CS, whereas the conegativities were 98 and 97%, respectively. Sera from xenodiagnosis-positive dogs and cats also reacted by TIA (copositivities of 97 and 83%, respectively). TIA was reactive in three CS-negative samples and was able to resolve results in two cat serum samples that were CS inconclusive. Our study is the first to describe the development of trans-sialidase neutralizing antibodies in naturally infected dogs and cats. High CS conegativity and the absence of trans-sialidase neutralization in dog sera from areas where leishmaniasis is not endemic and from dogs with visceral leishmaniasis support TIA specificity. The TIA may be a useful tool for T. cruzi detection in the main domestic reservoirs.